PENGARUH INSTRUMEN PEMBIAYAAN TERHADAP PROFITABILITAS PADA PT. BPRS AMANAH INSANI - Munir Munir; Abdul Kadir Abu; Rimi Gusliana Mais (Kopertais Wilayah I DKI Jakarta dan Banten, 2022)
PT. BPRS Amanah Insani has financing service instruments, namely murabahah financing, Mudharabah financing and musyarakah financing. The purpose of this study is to determine the effect of murabahah financing and Mudharabah financing on profitability. This research uses a quantitative approach. The data used in this study are secondary data. The data collection used is the quarterly financial statements of PT. BPRS Amanah Insani for the 2012-2021 period. The data analysis technique used in this study is multiple linear regression. From the multiple regression test, it was concluded that murabahah financing has a negative and significant influence on profitability, while Mudharabah financing has no significant effect on profitability, this happens because mudharabah financing PT. BPRS Amanah Insani bears more of the costs that come out of the financing than the profits.